Health Program Planning, Implementation, and Evaluation : Creating Behavioral, Environmental, and Policy Change - Kreuter, Marshall W.; Peterson, Darleen V.; Ottoson, Judith M.; Gielen, A. C. (Andrea Carlson); Green, Lawrence W. (Book collections on Project MUSE., 2022)
"This textbook covers program planning and evaluation for public health. Population health planning should begin with an assessment of the social needs and quality of life concerns of the community and then systematically identify the epidemiology of health problems and their behavioral and environmental determinants"--